2020
DOI: 10.1002/mp.14543
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodules risk stratification through deep learning based on ultrasound images

Abstract: Purpose Clinically, the risk stratification of thyroid nodules is usually used to formulate the next treatment plan. The American College of Radiology (ACR) thyroid imaging reporting and data system (TI‐RADS) is a type of medical standard widely used in classification diagnosis. It divides the nodule’s ACR TI‐RADS level into five levels by quantitative scoring, from benign to high suspicion of malignancy. However, such assessment often relies on the radiologists’ experience and is time consuming. So computer‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The novel AI TI-RADS had better accuracy than ARC TI-RADS when performed by inexperienced radiologists (55% vs. 48%) and experts (65% vs. 47%). Similar to other studies, ARC TI-RADS-based classifiers had higher sensitivity and slightly lower specificity ( 21 24 ). Wu et al.…”
Section: Applications Of Ai In the Us Diagnosis Of Tnsupporting
confidence: 87%
“…The novel AI TI-RADS had better accuracy than ARC TI-RADS when performed by inexperienced radiologists (55% vs. 48%) and experts (65% vs. 47%). Similar to other studies, ARC TI-RADS-based classifiers had higher sensitivity and slightly lower specificity ( 21 24 ). Wu et al.…”
Section: Applications Of Ai In the Us Diagnosis Of Tnsupporting
confidence: 87%
“…All the evaluated studies showed significant high overall diagnostic accuracy of CNNs, above 90%, which does not differ much from that of expert radiologists. In particular, most of the studies demonstrate a comparable diagnostic accuracy, such as Watkins et al, Bai et al, Ye et al, Koh et al, and Fresilli et al [ 4 , 16 , 20 , 30 , 40 ]. Approximately the same number of studies demonstrate a higher diagnostic accuracy of AI systems compared to that of expert radiologists (e.g., Sun et al, Peng et al, and Zhou et al) [ 15 , 22 , 23 ], or vice versa, a superiority of diagnostic accuracy by expert radiologists compared to that of AI systems (e.g., Zhang et al and Han et al) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the world of DL, many authors are focusing on convolutional neural networks (CNNs), introduced by LeCun [ 65 , 66 ]. Before their diagnostic accuracy can be assessed, CNNs are trained by subjecting them to specific algorithm-segmented US images of thyroid nodules with known histological diagnosis; at the end of the learning phase the CNNs are able to analyze the captures of thyroid nodules and to suggest a risk stratification of these nodules in correlation to a specific TI-RADS level [ 16 ]. Most of the existing literature evaluates the diagnostic accuracy of various types of properly trained convolutional neural networks by comparing them to those of radiologists with variable degrees of experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjectivity of diagnostic criteria to each sonographer may also result in a poor interobserver agreement. An alternative approach would be the use of the computer‐aided diagnosis (CAD) system, which has been applied in various diseases in the past few decades and achieved outstanding performance in most cases 16–20 . Recently, deep learning with convolutional neural networks (CNNs) has been gaining attention with respect to pattern recognition of images and as an artificial intelligence strategy used in CAD systems as it has distinct advantages over traditional machine learning methods in providing an end‐to‐end feature extraction and efficient classification framework to free users from the troublesome handcrafted feature extraction 21–24 .…”
mentioning
confidence: 99%